Development of a Web-Based Digital Dictionary for the Most Common Vocabulary in the Qur'an - Dhimas Hidayat; Aris Rakhmadi (The IJICS (International Journal of Informatics and Computer Science), 2026)
Access to learning the most common Quranic vocabulary remains a challenge, particularly for the Deaf and Hard of Hearing community who face a significant lack of inclusive digital resources. Existing digital dictionaries often overlook this demographic, failing to provide crucial accessibility features such as sign language video translations. This research aims to bridge this accessibility gap by designing and developing a specialized, website-based digital dictionary focused on the most common Quranic terms. The primary contribution is an interactive and inclusive platform that integrates Arabic script, transliteration, and meaning with corresponding sign language video interpretations. The Agile Development methodology was employed, allowing for a flexible and iterative process to effectively address user feedback. This lifecycle involved key stages such as requirements planning, system modeling using UML and ERD, backend development with the Laravel framework, and functional validation via black-box testing. The testing phase demonstrated highly positive outcomes; functional validation via Black-Box testing confirmed that all system modules operated correctly according to specifications without any errors. Furthermore, the usability evaluation using the System Usability Scale (SUS) yielded an average score of 71, placing the platform in the "Good" category with an "Acceptable" level of usability.